Pelvic abscess due to Mycoplasma hominis following caesarean section. Issue 4 (August 2016) - Mori, Nobuaki; Takigawa, Aya; Kagawa, Narito; Kenri, Tsuyoshi; Yoshida, Shinji; Shibayama, Keigo; Aoki, Yasuko
Abstract : Introduction: Mycoplasma hominis is associated with genito-urinary tract infection and adverse pregnancy outcomes. However, whether the species is a true pathogen or part of the genito-urinary tracts natural flora remains unclear. Case presentation: A 41-year-old pregnant woman was admitted to our hospital at 38 weeks and 5 days of gestation owing to premature rupture of the membranes. The patient delivered by caesarean section. Subsequently, the patient complained of lower abdominal pain and had persistent fever. Enhanced computed tomography revealed pelvic abscesses. Gram staining of pus from the abscess and vaginal secretions indicated presence of polymorphonuclear leucocytes but no pathogens. Cultures on blood agar showed growth of pinpoint-sized colonies in an anaerobic environment within 48 h. Although administration of carbapenem and metronidazole was ineffective and we could not fully drain the abscess, administration of clindamycin led to clinical improvement. The isolates 16S rRNA gene and yidC gene sequences exhibited identity with those of M. hominis. Conclusion: Physicians should consider M. hominis in cases of pelvic abscesses where Gram staining yields negative results, small colonies are isolated from the abscess and treatment with β-lactam antibiotics is ineffective.